Rare slow channel congenital myasthenic syndromes without repetitive compound muscle action potential and dramatic response to low dose fluoxetine - Durmus, Hacer; Sticht, Heinrich; Ceylaner, Serdar; Hashemolhosseini, Said; Deymeer, Feza (Acta Neurologica Belgica, 2020)
Congenital myasthenic syndromes are rare hereditary disorders caused by mutations associated with proteins of the neuromuscular junction. Abnormal ‘‘gain of function’’ mutations result in prolonged nicotinic acetylcholine receptor channel open state causing a rare subtype of CMS, slow-channel CMS (SCCMS). Mutations in the delta subunit encoding the gene, CHRND, resulting in SCCMS are extremely rare. An important clue to the diagnosis of SCCMS is repetitive CMAP’s. Fluoxetine, usually at high doses, is used to treat SCCMS. The mutation, recently described in one patient, was identified by whole exome sequencing and validated, and its segregation with the disease was ascertained by Sanger sequencing. Here, we describe clinical and genetic findings of an early onset SCCMS patient carrying a very rare missense mutation c.880C > T in CHRND causing a highly conserved leucine to phenylalanine substitution in the M2 domain of CHRND. The patient had no repetitive CMAP. He had a dramatic response to fluoxetine at low–moderate doses (40 mg/day), increasing over months: Being wheelchair bound, he could walk independently after treatment. Rare cases may offer insight into the pathological gating mechanism leading to CMS. SCCMS should be suspected even without a repetitive CMAP. Fluoxetine at relatively low doses can be a very effective treatment.
CRIS-Team Scopus Importer:2020-10-16
Keywords: AChR delta subunit; CHRND; Congenital myasthenic syndromes; Fluoxetine; Slow channel